POTENSI PERDAGANGAN INTERNASIONAL TERHADAP PERTUMBUHAN EKONOMI INDONESIA DI MASA MENDATANG - Alfiya Gita Pramadani; Carissa Aurelia Stanis; Christoper Ondihon Sidabutar; Nabila Salwa Dita (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
International trade greatly affects a country's economic growth. One of the indicators for reviewing a country's economic growth is to look at the country's Gross Domestic Product (GDP). GDP is the accumulation of all market value generated by a country for the production of goods and services in a certain period. In GDP, there are results of calculating the value of export and import activities that affect the size or size of the country's GDP. The more exports of a country increase, the income of that country will also increase. This is also in line with the theory of international trade proposed by Heckscher-Ohlin which states that Net-Export or net export is one of the most important factors of Gross National Product (GNP), so that with changes in the value of Net-Export it will have an influence on changes in national income.The research method used in this study is to use qualitative descriptive analysis. This method is carried out by describing the phenomena that occur as a result of international trade carried out by Indonesia on Indonesia's economic growth. The data used in this study is data obtained from the analysis of various sources and journals with a vulnerable time of 2017 - 2022.